From disbandment to sustainable peace: Threat and risk analysis of Jemaah Islamiyah in Lampung, Indonesia - I Made Astawa; Jindar Muttaqin; Mochammad Wahyu Ghani (SIMULACRA: JURNAL SOSIOLOGI, 2026)
This research analyzes the effectiveness of the synergy between hard and soft approaches in facilitating the disbandment of Jemaah Islamiyah (JI) in Lampung Province and maps the residual risks following its dissolution Utilizing a qualitative case study method with purposive and snowball sampling, the study involved 33 key informants from diverse backgrounds. The results reveal a four-stage transformation roadmap: structural disruption (2019–2022), ideological intervention (2022–2023), agricultural economic empowerment (2023–2024), and a collective declaration of disbandment in August 2024. This synergy effectively degraded operational capabilities and transformed members' ideological consciousness through dialogue and sustained economic reinforcement. However, the study identifies residual threats in the form of persistent social networks and emotional ties among former members. The formal disbandment marks only the beginning of a complex reintegration phase requiring cross-institutional strategies and community support to preventrecidivism. This study contributes a contextual post-organizational analysis of radical group transformation rarely addressed in existing counterterrorism literature.